Configuring the Performance Measurement Systems of Small Medium Enterprises from the Life Cycle Perspective - Sofiah Md Auzair,; Amizawati Mohd Amir,; Zulaihan Ismail, (2019)
The purpose of this paper is to examine the attributes of Performance Measurement Systems (PMS) of the Malaysian Small Medium Enterprises (SMEs), from an organizational life-cycle perspective. It was suggested that PMS is less comprehensive at birth stage, most comprehensive in the growth stage and decrease at the maturity stage of the life-cycle. The more comprehensive use of PMS is expected to be associated with higher organizational performance. Survey questionnaires were administered to managers yielding 90 usable responses. Using cluster analysis, SMEs were categorized into birth, growth and maturity stages. The findings support the hypotheses and thereby provide evidence on the variations of PMS attributes among SMEs across the life cycle stages. The study contributes to knowledge on internal consistencies between organizational factors at each organizational life-cycle stages that has implications for management control systems. To the practice, it provides evidence on organizational adaptations to changes in firm’s strategy and structure. (Abstract by authors)